Rol' oksidativnykh protsessov v obrazovanii sportivnogo tsellyulita i mikrotravmatizma u sportsmenov (gipoteza) - Topuzov, I. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The investigations upon athletes had shown that the typical cellulite of the "women pool" is considerably less found in them. At the same time there is the cellulite in athletes from the both genders in their most overloaded body zones. The author named this type of cellulite, related to the most intensively overloaded body zones "sports cellulite". The hard physical exercises are prerequisite for the formation of cellulite. This is mostly due to the oxidative stress - increase of the harmful Oxigen Free Radicals /OFR/and switching of the specific vicious circle of the cellulitogenesis. The cellulite speeds up the degeneration of the tissues, embarrasses the regular circulation and draining, leads to early growing old of the cells and tissues of the affected muscles and joints - microtraumatism. Then the very intensive physical exercises are also a prerequisite for the simultaneous formation of the cellulite and microtraumas. The diagnostics of cellulite of the sportsmen could be used as a screening check-up for the discovering of not yet revealed microtraumas.